2008
DOI: 10.1097/rct.0b013e318161dc58
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Computed Tomographic Assessment of Early Hepatocellular Carcinoma in Cirrhotic Liver Disease

Abstract: Preliminary results suggest that in patients with cirrhosis and early HCC, perfusion CT is a feasible technique for noninvasive assessment of tumor vascularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…The differences of the cited parameters were statistically significant (P < 0.001), with the only exception of BV. As also reported in our previous studies [15,16], AP (the arterial fraction of blood flow) could be the most representative perfusion parameters for the evaluation of residual tumor-associated neoangiogenesis. Indeed, AP is directly related to the presence of residual or new arterial unpaired vessels within the ablated area, which sustain tumor regrowth after treatment.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The differences of the cited parameters were statistically significant (P < 0.001), with the only exception of BV. As also reported in our previous studies [15,16], AP (the arterial fraction of blood flow) could be the most representative perfusion parameters for the evaluation of residual tumor-associated neoangiogenesis. Indeed, AP is directly related to the presence of residual or new arterial unpaired vessels within the ablated area, which sustain tumor regrowth after treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Tissue enhancement depends on tissue iodine concentration and therefore is an indirect reflection of tissue vascularity and vascular physiology [13]. In recent years, CT-p has been shown to provide information useful for lesion characterization and assessment of tumor grade, providing an in vivo marker of neoangiogenesis [12,15]. Other studies have recently evaluated the potential usefulness of CT-p even for therapy monitoring, both after antiangiogenic drugs and transarterial chemoembolization (TACE) in several neoplastic diseases like HCC [13,[16][17][18][19].…”
mentioning
confidence: 99%
“…Preliminary studies have shown that vascularization decreases with TACE treatment [42,46] and with targeted agents such as bevacizumab [47,48], with remaining viable tumour showing higher flow values [41] These changes may occur 10-12 days after treatment initiation and higher baseline extraction fraction may be found in responders [47]. The technique was reproducible with good correlation between repeat examinations (r00.9, p<0.01) in a small number of patients (n04) in one study [39].…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 93%
“…Arterial blood flow was high with a sensitivity and specificity of detection of 86% and 65% within 11 weeks of tumour induction even though only 7% was visible by eye [38]. A small number of singlecentre human studies have shown the feasibility of DCE CT in HCC for detection and vascular response assessment [39][40][41][42][43][44][45][46][47]. HCC typically shows an increase in arterial liver perfusion (Fig.…”
Section: Assessment Of Tumour Vascularizationmentioning
confidence: 99%
“…However, this procedure is often used to help confirm liver transplant eligibility by excluding extrahepatic tumor (16,17).…”
mentioning
confidence: 99%